The Utilization of Bioorganic Mixture Ferns Gleichenia linearis (Burm.) Clarke and Leave Manure Leaves of the Pine merkusii Jungh et de vriese as a Medium Jabon Seedling (Anthocephalus cadamba miq.) - Yadi Setiadi; Yolandari Yolandari; Nina Mindawati (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Planting medium that’s commonly used in the nursery ground is a top soil. Top soil that is utilized as a medium for planting is known have some weakness and may result in environment damage when used on an ongoing basis, thus the use of additional materials materials top soil that qualify as planting media needs to be done. One of the materials that can be used as a medium for planting is fern nor diacritical marks (Gleichenia linearis) leaf litter and pine (Pinus merkusii). These materials can be used as a medium for planting after compostion process to remove content of cellulose and hemicellulose contained in such materials. Nutrient element content is inside planting medium also be added to handouts fertilizers. Utilization bioorganic as media addition to jabon seedlings are known can reduce the use of plant top soil as a medium of 50% and produce seedling growth (5.8 cm high; diameter 0,5 mm) while same either by medium planted in top soil (6,5 cm high; diameter 0,5 mm) while seedling on bioorganic planting medium has on media cropping bioorganik having less good growth (high 4,3 centimeters; diameter 0,4 mm ) gord ratio C/N still very high that the mineral content that is not available in the media and cannot be used by plant. Provision of fertilizer Terabuster 1% Bioremedi 2%, also a mixture of Terabuster and Bioremedi, respectively, as many as 20 ml are known to be able to boost the growth of the jabon seedling about 10-50% compared with non-fertilization, besides fertilizers were also able to increase the percent living seed planting in jabon Bioorganic medium about 4-21%